209k views
0 votes
Simplify the following expression. (3m/4-2)+8 A. 8m/4 B. 9m/4 C. 3m+24/4 D. 3m+28/4

Simplify the following expression. (3m/4-2)+8 A. 8m/4 B. 9m/4 C. 3m+24/4 D. 3m+28/4-example-1
User Cshah
by
5.6k points

2 Answers

2 votes
Answer: C

Step-by-step explanation:

(3m/4 - 2) + 8
= (3m/4 - 8/4) + 8
= (3m - 8)/4 + 32/4
= (3m - 8 + 32)/4
= (3m + 24)/4

Therefore the answer is C
User Lfboulanger
by
5.3k points
1 vote

Answer:

C

Step-by-step explanation:

Given

(
(3m)/(4) - 2 ) + 8 ( remove parenthesis )

=
(3m)/(4) - 2 + 8

=
(3m)/(4) + 6

=
(3m)/(4) +
(24)/(4) ← add the numerators leaving the denominator

=
(3m+24)/(4) → C

User Feathj
by
5.4k points